DEVELOPMENT OF PSYCHOLOGICAL MECHANISMS OF FORMATION OF COPING BEHAVIOR FACTORS IN ADOLESCENTS - Nosirova Sitorabonu Alisher qizi (Journals Park Publishing, 2023)
Adolescent cognitive and behavioral factors of coping are under active development.The purpose of this review is to explore the concept of coping in adolescence.
Keywords: Coping Behavior, Coping Strategy, Coping, Adolescent.